2014
DOI: 10.1103/physreve.90.062203
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the vertical plunging force of a spherical intruder into a prefluidized granular bed

Abstract: The plunging of a large intruder sphere into a prefluidized granular bed with various constant velocities and various sphere diameters is investigated using a state-of-the-art hybrid discrete particle and immersed boundary method, in which both the gas-induced drag force and the contact force exerted on the intruder can be investigated separately. We investigate low velocities, where velocity dependent effects first begin to appear. The results show a concave-to-convex dependence of the plunging force as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Figs.2 and 3 show the vertical position z(t) and speed v i (t) of the intruder, obtained experimentally and numerically, respectively. For the experimental cases, the initial speed is estimated from a parabolic fit of the intruder trajectory before impact together with the initial falling height H. As noted, in all cases the intruder dynamics predicted numerically is in very good quantitative agreement with the experimental results and in line with previous findings 20,[32][33][34] .…”
Section: Intruder Dynamicssupporting
confidence: 84%
“…Figs.2 and 3 show the vertical position z(t) and speed v i (t) of the intruder, obtained experimentally and numerically, respectively. For the experimental cases, the initial speed is estimated from a parabolic fit of the intruder trajectory before impact together with the initial falling height H. As noted, in all cases the intruder dynamics predicted numerically is in very good quantitative agreement with the experimental results and in line with previous findings 20,[32][33][34] .…”
Section: Intruder Dynamicssupporting
confidence: 84%
“…Many experiments and simulations show that, at steady state (see below) F z (z) = kz α , but there is no consensus on the value of α. Hill et al, 23 and Peng et al 24 found α = 1.3 while Hou et al 25 , Durian et al 12,19,26 , Lohse et al 27 and Kang et al 28 measured α = 1 experimentally, although the latter also showed and discussed an initial regime for z < z c . Simulations by Xu et al 16 also support α = 1.0.…”
Section: Introductionmentioning
confidence: 76%
“…The main aim of this sub-section is to benchmark the simulation code by calculating the granular drag force in packed bed. In literature (Lohse et al 2004); Katsuragi and Durian 2007;Xu et al 2014), this problem is reasonably studied and the relation for modeling granular drag force can be written as: , In some work, is included in rather than as a separate term (Katsuragi & Durian 2007). For intruders with relatively smaller velocities (i.e.…”
Section: Drag Force On Intruder Without Fluidization Of Granular Matementioning
confidence: 99%
“…(this value of for ignoring and the relation for in Eq. 14are obtained from literature (Lohse et al 2004;Katsuragi & Durian 2007;Xu et al 2014;Hou et al 2005;Hill et al 2005) (16) Lohse et al (2004) proposed the value of =13.3 0.5 N/m and =1 using experiments of free fall of large object in loosely packed sand. Hill et al (2005) using the plunging and retraction experiments of intruders into granular material proposed the value of =15 3 N/m and =1.3.…”
Section: Drag Force On Intruder Without Fluidization Of Granular Matementioning
confidence: 99%